Explaining the fame of Friedman's presidential address - Forder, J; Sømme, K (Oxford University Press, 2019)
It is noted that although in fact it lacks the revolutionary content commonly ascribed to it, Friedman’s Presidential Address to the American Economic Association is very highly regarded as an original and formative contribution. It is argued that close attention to the literature shows it was not initially seen as original, and only after an interval of five years did the idea of its revolutionary status retrospectively, but suddenly become widely accepted. The explanation of this change of view is considered. Four explanations are suggested: one involving terminological confusion; one involving a change of theoretical priorities; and two involving debates of the 1970s which, although they did not in fact do so, appeared to build on Friedman’s presentation, and by this appearance gave it an undeserved stature.